Dampak Penurunan Harga Kerajinan Tangan Terhadap Minat Produksi Pengerajin di Desa Beleka Lombok Tengah - Lena Susanti (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Handicrafts are an important part of the creative economy sector in Indonesia. The creative economy itself is an activity based on the use of intellectual property to create creativity, which aims to increase skills and income. The formulation of this research is that this research aims to determine the impact of the decrease in selling price on the production interest of artisans in Beleka Village and the factors causing the price decrease. This study uses a qualitative approach with a type of field research, subjects are selected purposively, with data collection techniques through observation and interviews. The validity of the data was tested using source triangulation, while data analysis was carried out through the stages of collection, reduction, presentation, and drawing conclusions. The results of the study show, first, the decline in the price of handicrafts in Beleka Village has a great influence on the enthusiasm and interest of artisans to stop producing. This is due to low selling prices and imbalances with the increase in raw material costs, which ultimately reduces profits. Second, Second, the decline in the price of handicrafts in Beleka Village is caused by several main factors. One of them is competition with bulk products that are cheaper and easily accessible in the market. In addition, changes in consumer tastes who tend to choose modern and practical products also contribute to reducing interest in traditional crafts.